Novo índice para avaliação da estenose dos seios transversos para diagnóstico de hipertensão intracraniana idiopática - Carvalho, Gustavo Balthazar Da Silveira [UNIFESP] (2017)
Objective: To assess the role of venous magnetic resonance imaging (MRI) in the detection of transverse sinus stenosis and the importance of this finding in idiopathic intracranial hypertension (HII), and to propose an index that contributes to this diagnosis. METHODS: We retrospectively assessed the exams of patients over the age of 18 who were followed at our institution's pseudotumor ambulatory, who underwent intracranial venous ARM exams from January 2010 to July 2012. The exams were randomly analyzed by 3 radiologists. The evaluators classified the stenosis in the right and left transverse sinuses separately, according to the graduation: 0-normal; 1- Stenosis up to 1/3 (<33%); 2- Stenosis between 1/3 and 2/3 (33-66%); 3 - Stenosis above 2/3 (> 66%) and 4 - Hypoplasia or agenesis. We established an index based on the multiplication of the numbers of this degree of stenosis of each transverse sinus. Point and interval estimation of the sensitivity, specificity and area under the ROC curve were obtained to obtain cutoff points for the index in order to distinguish patient controls. Results: The sample selected in this study consisted of 63 individuals, 32 (50.8%) of the group with diagnosis of HII [31 (96.9%) women and only 1 (3.1%) men] and 31 ( 49.2%) of the control group. The HII group had a higher degree of stenosis when compared to the control group, for all examiners. Values ​​greater than or equal to 4 for diagnosis of HII indicated a sensitivity of 94.7% and specificity of 93.5% Conclusion: We believe that MRA should be included in the evaluation of patients with suspected IBD and bilateral stenosis of the transverse sinus should be valued for diagnosis. The index proposed in this study to classify this stenosis proved to be a fast and accessible method for the diagnosis of IBD.